The influence of work family conflict and fuel subsidy removal on tax compliance: A proposed framework for small and medium enterprises - Ayuba, Augustine; Saad, Natrah; Zainal Affrin, Zaimah (2015)
Several factors have been suggested to influence tax compliance behaviour.To date, some of the factors that have been considered include economic and noneconomic.Despite these studies, however, few studies have attempted to consider the influence of work family conflict and fuel subsidy removal on tax compliance behaviour.This paper proposes work family conflict and fuel subsidy removal to influence the compliance behaviour of the SMEs taxpayers.The proposed model will have several critical implications for understanding the factors that may influence the behaviour of the SMEs taxpayers.